Clarendon Palace. The History and Archaeology of a Medieval Palace and Hunting Lodge near Salisbury, Wiltshire - Beaumont James, Tom (Reports of the Research Committee of the Society of Antiquaries of London, 1989)
This volume gives an account of all the excavations undertaken at Clarendon in the twentieth century, including those of 1933-9 led by John Charlton and Tancred Borenius and the excavations by Elizabeth Eames and John Musty in the 1950s and 1960s. The history, archaeology and finds are examined together for the first time to present a detailed picture of palace life.